PENERAPAN PEMBELAJARAN KOOPERATIF MODEL KARTU ARISAN UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN REAKSI REDUKSI DAN OKSIDASI DI KELAS X SMA NEGERI 5 PEKANBARU - Iswarti, Noni Iswarti; Erna, Maria Erna; Amran, Elva Yasmi Amran Yasmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Detailed examination has been completed about subject reduction and oxidation in class X SMAN 5 Pekanbaru. This research aims to increase student achievement on the subject reduction and oxidation in class X SMAN 5 Pekanbaru.  This research is a kind of experiment research with pretest-posttest design. The research was conducted in SMAN 5 Pekanbaru. The samples of this research were the students of class X1 as the experimental class and  students of class X2 as  the control class. Experimental class is a class that is applied  the application. Data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic> ttable is 5,53 > 1,67. The conclusion of examination is the application of lottery card model can improve student achievement on the subject of atomic structure class X SMAN 5 Pekanbaru, increase learning of 29,62%. Key Words : Learning Achievement, Lottery Card Model, and Reduction and Oxidation